Financial Literacy and Retirement Planning among Government Officers in Malaysia - Tan, Shirley; Singaravelloo, Kuppusamy (Taylor & Francis, 2020)
This study examines the level of financial literacy, financial behaviour and retirement planning behaviour and its dynamics among Malaysian government officers involving 320 employees working in the federal government administrative centre in Putrajaya and Kuala Lumpur using a questionnaire. Findings show high level of financial literacy, good financial behaviour but a mediocre in retirement planning behaviour, and only education and personal income positively influence financial literacy. Age and gender of officers do not influence financial literacy. Furthermore, financial literacy does not correlate with retirement planning and neither does it mediate the relationship between financial behaviour and retirement planning. © 2019, © 2019 Taylor & Francis Group, LLC.